Legal Status of Religious Communities in Socialist Yugoslavia - Đukić, Dalibor B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
After the Second World War, Yugoslavia, like other communist regimes, implemented the separation of church and state, coupled with an aggressive secularization that permeated all aspects of society. However, the Yugoslav model of state-religion relations diverged from the typical communist approaches in Eastern Europe. This paper analyzes this unique model by examining the influence of three key factors. The first factor is time. The Yugoslav state's approach to religion evolved over time, shifting from widespread persecution of believers and religious officials to a more cooperative stance, eventually leading to agreements that regulated the rights of specific religious organizations. This paper tests the thesis that, over time, the Yugoslav model gradually moved away from abolitionist system of complete religious freedom restriction towards a model of secular control over religious organizations with a strict separation of church and state. The second factor is territory. In the field of ecclesiastical law, it is widely recognized that identifying the model of state-religion relations within a single state can be a complex task, particularly in federations where the regulation of religious freedom is often devolved to federal units. This paper examines the extent to which the implementation of the Yugoslav model varied across different federal units, how these practices were reflected in legal norms, and what the causes and consequences of these differences were. Finally, the third factor is the subjects of religious freedom. While the principle of equal treatment for all religious organizations should theoretically apply in models of church-state separation, this was not always the case in Yugoslavia. The state's treatment of religious organizations was not uniform, and this paper explores how these disparities were regulated and the underlying reasons for such practices.
Keywords: religious communities; freedom of religion; separation of church and state; Yugoslavia; concordat; the pulpit law